1979
DOI: 10.1111/j.1600-0528.1979.tb01201.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of multiple approaches to dental health education

Abstract: An evaluation was made of the separate effects on oral hygiene of token reward treatments, discovery (project) learning, and plaque staining feedback demonstrations with children in the first through fifth grades. Both short- and long-term effects were assessed in an open classroom setting. Twenty classrooms were non-randomly assigned to treatment and control groups. Plaque scores were recorded according to the Podshadley Patient Hygiene Performance Index (PHP) at time T0, before initiation of any of the educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(15 reference statements)
2
4
0
Order By: Relevance
“…Both interventions were found effective in improving oral health behavior and attitude. This finding is in accordance with other studies that found that oral health behavior and attitude of primary school children to temporary improve regardless of the educational approach used [ 8 , 11 , 26 , 39 ]. Some other studies, found no improvement when using the traditional methods [ 15 , 40 ] in contrast to the finding of the present study; however, neither the present oral health education program managed to sustain the improved oral health attitude and behavior in the long-term.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Both interventions were found effective in improving oral health behavior and attitude. This finding is in accordance with other studies that found that oral health behavior and attitude of primary school children to temporary improve regardless of the educational approach used [ 8 , 11 , 26 , 39 ]. Some other studies, found no improvement when using the traditional methods [ 15 , 40 ] in contrast to the finding of the present study; however, neither the present oral health education program managed to sustain the improved oral health attitude and behavior in the long-term.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding clinical data, experiential learning group showed improved oral hygiene as previously found when using experiential learning techniques [ 5 , 6 , 8 ]. However, the improvement was temporary which is in accordance with the findings of other studies [ 5 , 6 , 8 - 10 , 15 , 34 , 39 , 42 , 43 ]. In the traditional lecturing group, no statistically significant improvement has been found even for the short term, suggesting that experiential learning is a more effective method for oral hygiene instruction.…”
Section: Discussionsupporting
confidence: 92%
“…The results are in agreement with those of other studies that have shown an improvement in oral health knowledge after the introduction of a school programme [21][22][23]26,43,44 . The improvement in knowledge and associated behaviours is common when measured immediately after interventions 24,27,43,45 . The sustainability of knowledge and behaviours, however, is known to be difficult to achieve over the long term 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in knowledge and associated behaviours is common when measured immediately after interventions 24,27,43,45 . The sustainability of knowledge and behaviours, however, is known to be difficult to achieve over the long term 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether token reinforcement plus minimal instruction would be of value over a similar treatment period and follow-up, Kaplis et al (1979), investigated one group of children who brushed their teeth at home and another who did rh is in school These children and a third group who received no reinforcements, used an ultra-violet light to show up plaque on their teeth. A fourth group participated in dental education projects in class while a fifth group had no dental instruction.…”
Section: Preventive Programmesmentioning
confidence: 99%